Pengembangan Sistem Pembayaran pada Website Bimbingan Belajar Non-Formal Berbasis PHP MySQL di LOOP Coding BSD, Tangerang, Banten - Arika Karpina; Yuma Akbar; Widya Ayu Lestari; Fitriani Noer Jamilah (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2025)
This study develops a web-based payment system using PHP and MySQL to overcome the problem of manual recording in course institutions. Many course places still use manual recording that is prone to errors, administrative delays, and difficulties in making financial reports. This system aims to improve efficiency and accuracy by providing a more structured administration solution. Features such as dashboards, monthly and annual payment monitoring, and financial data recaps allow for transparency and more effective data management. The implementation of the system at Loop Coding BSD, Tangerang, has been proven to speed up the recording process, reduce manual errors, and improve financial reports. This system improves operational efficiency, data security, and facilitates evaluation or auditing. Overall, the implementation of this web-based system makes it easier to manage payment data and supports smooth administration and financial management in educational institutions.